2021
DOI: 10.1007/s00011-021-01522-6
|View full text |Cite
|
Sign up to set email alerts
|

H. pylori CagA activates the NLRP3 inflammasome to promote gastric cancer cell migration and invasion

Abstract: Objective The CagA (cytotoxin-related gene A, CagA) protein is an important factor for the pathogenicity of Helicobacter pylori (H. pylori). Although H. pylori has previously been shown to activate the NLRP3 inflammasome, it remains unclear what role CagA plays in this process. In the current study, we aimed to investigate the effect of CagA on NLRP3 activation and how it is linked to gastric cancer cell migration and invasion. Methods CagA positive H. pylori strain (Hp/CagA + ) and CagA gene knockout mutant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 34 publications
2
22
0
1
Order By: Relevance
“…However, the cytotoxin-related gene A (CagA) protein, an important pathogenic factor of Helicobacter pylori ( H. pylori ) [ 143 ], promotes the invasion and migration of GC cells by activating NLRP3 inflammasome, while the suppression of H. pylori -triggered inflammatory response and the depression of pyroptosis via the ROS/NLRP3/caspase-1/IL-1 β pathway may suppress the progression of GC [ 144 ]. These results indicate that there is a close and complex relationship between GC and pyroptosis, while more researches are necessary in future.…”
Section: Pyroptosis and Cancermentioning
confidence: 99%
“…However, the cytotoxin-related gene A (CagA) protein, an important pathogenic factor of Helicobacter pylori ( H. pylori ) [ 143 ], promotes the invasion and migration of GC cells by activating NLRP3 inflammasome, while the suppression of H. pylori -triggered inflammatory response and the depression of pyroptosis via the ROS/NLRP3/caspase-1/IL-1 β pathway may suppress the progression of GC [ 144 ]. These results indicate that there is a close and complex relationship between GC and pyroptosis, while more researches are necessary in future.…”
Section: Pyroptosis and Cancermentioning
confidence: 99%
“…The authors reported that CagA also participates in the generation of intracellular ROS and that ROS inhibition has the potential to disrupt the NLRP3 pathway and pyroptosis. With these findings, the authors concluded that NLRP3 plays a key role in the action of CagA on gastric cells and that silencing NLRP3 can limit the effects of migration and invasion of cancer cells caused by CagA[ 99 ].…”
Section: Role Of Caga In Gastric Carcinogenesismentioning
confidence: 99%
“…Also found that low expression or inhibited expression of gasdermin D (GSDMD) can promote tumour cell proliferation in GC. Zhang X et al ( Zhang et al, 2021 ). Showed that the H. pylori cytotoxin-related gene A (CagA) protein can activate the NOD-like receptor protein 3 (NLRP3) inflammasome pyroptosis pathway and promote GC cell migration and invasion.…”
Section: Introductionmentioning
confidence: 99%